If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3(2x+3)-7(x-4)=15x-11
We move all terms to the left:
3(2x+3)-7(x-4)-(15x-11)=0
We multiply parentheses
6x-7x-(15x-11)+9+28=0
We get rid of parentheses
6x-7x-15x+11+9+28=0
We add all the numbers together, and all the variables
-16x+48=0
We move all terms containing x to the left, all other terms to the right
-16x=-48
x=-48/-16
x=+3
| 48x+4)=176 | | 4(8x+4=176 | | 60/1.4=x | | 60/1.2=x | | 60/1.8=x | | 3x-2(5-x)=30 | | 0.2*60=x | | 0.8*60=x | | 1.2x*60=x | | 1.2x-60=x | | 1.8/x=60 | | 8(4-y)=6(3-y) | | 60*1.8=x | | 60-1.2x=x | | 60*1.2x=x | | a-12=43 | | 60-x=1.2x | | x^2-0.7*x^2=80 | | 60-x=1.4x | | 60-x=1.4 | | 60-x=1.8x | | 1+4x=16-x | | W^2+5w-200=0 | | 3x+4=2(7-2x) | | X^2+40x-319=0 | | 2^x/3=256 | | 7x-65=5 | | 6x-17=-11 | | 7x-13*7=5 | | 4(2x-28)-3(3x-7)+9(12-2)=0 | | -3x-2+6=2x+6-3 | | -3(x-2)+6=2(x+3)-3 |